2017
DOI: 10.4103/ua.ua_25_17
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy is associated with reduced continence outcomes following implantation of the artificial urinary sphincter in men with post-radical prostatectomy incontinence

Abstract: Objectives:The objective of this study is to present the outcomes of men undergoing implantation of artificial urinary sphincter, after treatment for prostate cancer and also to determine the effect of radiotherapy on continence outcomes after artificial urinary sphincter (AUS) implantation.Materials and Methods:A prospectively acquired database of all 184 patients having AUS insertion between 2002 and 2012 was reviewed, and demographic data, mode of prostate cancer treatment(s) before implantation, and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…[5][6][7][8] In contrast, other studies reported that a history of RT was associated with significantly worse outcomes, including continent status and complications after AUS implantation. [9][10][11][12][13] To date, there have been no studies investigating the impact of a history of pelvic RT on LUTS other than UI after AUS implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] In contrast, other studies reported that a history of RT was associated with significantly worse outcomes, including continent status and complications after AUS implantation. [9][10][11][12][13] To date, there have been no studies investigating the impact of a history of pelvic RT on LUTS other than UI after AUS implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated that there were no significant differences in urge incontinence, QOL, and complications after AUS implantation between patients with and without a history of pelvic RT 5–8 . In contrast, other studies reported that a history of RT was associated with significantly worse outcomes, including continent status and complications after AUS implantation 9–13 …”
Section: Introductionmentioning
confidence: 99%
“…19,20 Similarly, the effectiveness of AUS is reduced in radiated patients. 21 Besides, the histological alterations produced by radiation increase the risk of surgical revision due to urethral atrophy and erosion produced by the circumferential dissection of the urethral bulb for AUS implantation. 22,23 Irradiated patients may also suffer from the condition termed 'devastated bladder outlet', used to describe the combination of stress incontinence and stenosis of the membranous urethra and/or bladder neck.…”
Section: Discussionmentioning
confidence: 99%
“…Fixed retro‐urethral slings are not recommended for the very high rate of incontinence recurrence due to inadequate urethral closure caused by urethral and periurethral fibrosis 19,20 . Similarly, the effectiveness of AUS is reduced in radiated patients 21 . Besides, the histological alterations produced by radiation increase the risk of surgical revision due to urethral atrophy and erosion produced by the circumferential dissection of the urethral bulb for AUS implantation 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Some patient characteristics may influence efficacy outcomes, such as the cure, improvement and failure rates at the number of pads per day. First, we hypothesize that patients who received pelvic radiotherapy will have worse outcomes than non-irradiated patients due to fibrosis and scarring 40 42 . Second, we hypothesize that patients suffering from severe PPI will have worse outcomes following continence surgery than patients suffering from mild and moderate PPI 43 , 44 .…”
Section: Study Recordsmentioning
confidence: 99%